Narrating the Beauty Myth of Feminine Body Aesthetics in Classic Nepali Songs - Rai, Jiwan Kumar (JODEM: Journal of Language and Literature, 2023)
This paper analyzes the most celebrated classic Nepali songs of all time – “Gaajalu Tee Thulaathulaa Aankhaa”, “Lolaaeka Tee Thulaa Timraa Dui Najarale”, “Timeelaai Ma Ke Bhanu”, and “Rhritu Harumaa Timee” – the former two songs are penned by M.B.B. Shah, the next one is by Dipak Jangam, and latter one is by Rajendra Rijal. These songs are sung by Gulam Ali, Narayan Gopal, and Arun Thapa respectively. This study aims to explore the mythical narratives of the mainstream feminine body aesthetics embedded in the songs – large and deep black eyes, long black eyebrows, long black blond hair, thin lips, delicate, white skin complexion, attractive, shy, and etc. – that are guided and constructed from the frame of the aesthetic standard that is set by mainstream patriarchal culture. The researcher has used the textual analysis method to analyze the selected texts. Roland Barthes’s concept of myth has been applied as a theoretical tool for the critical analysis of the selected songs to achieve the set objectives. As Barthes argues, myths are meta-language through which dominant and ruling power communicates its ideological standpoints and attempts to naturalize them. They function as a complex hierarchical semiotic register where the signifier transfers from first order referents of meaning to second order. As the songs are fabricated cultural products and myth narratives, they not only entertain the audience, but also innocently impose and disseminate the contingent ideas or ideologies that they carry. At the same time, they marginalize the feminine body aesthetics of minority groups who do not belong to the mainstream community. This study helps look critically at Nepali songs and any cultural products leading to rethinking and redefining the dominant body aesthetics and standardization.